(untitled) (Archives of The Medicine and Case Reports, 2024)
Hypertension, a major risk factor for cardiovascular disease, poses a significant health challenge, particularly among the elderly. The "GAME BUSRI" intervention, promoting celery leaf consumption, offers a promising complementary therapy for blood pressure management. This study aimed to evaluate the effectiveness of this community-based intervention in reducing blood pressure among hypertensive elderly individuals in Purwakarta, Indonesia. A quasi-experimental pretest-posttest control group design was employed. Participants were recruited from the community and assigned to either the intervention group (receiving daily celery leaf decoction and health education) or the control group (receiving health education only). Blood pressure measurements were taken at baseline and after the 8-week intervention period. Data were analyzed using appropriate statistical tests. The intervention group demonstrated a statistically significant reduction in both systolic and diastolic blood pressure compared to the control group. The mean reduction in systolic blood pressure was 11.33 mmHg (p < 0.001), and the mean reduction in diastolic blood pressure was 8.67 mmHg (p < 0.001). No adverse events were reported. The "GAME BUSRI" intervention effectively reduced blood pressure in hypertensive elderly individuals. This community-based approach, utilizing a readily available and culturally acceptable resource, holds promise for improving hypertension management and reducing cardiovascular risk in this population.